NMR spectra of Azobenzene-bridged calix [8] arene complexes by ab initio hartree-fock calculations as nanostructure compound - Sayadian, Masoumeh; Sadegh, Hamidreza; Ali, Gomaa A. M. (Islamic Azad University-Tonekabon Branch, 2018)
Calix[8]arenes of conformational rigid were isolated. The NMR parameters of the structure of calix[8]arenes have been compared. The study of organic structures to form nanoporous materials is well-known in chemistry phenomena to find the crystal form of calix[8]arene as supramolecule. Investigated and compared hydrogen bonding, oxygen and nitrogen atoms effect on calix[8]arene and its complexes were reported at Hartree-Fock (HF) theory by Gaussian 2003 of program package. In this work, the complexing properties of azobenzene-bridged calix[8]arene with alkali earth metal cations has studied. The complexation properties of calix[8]arene were studied by HF method. The complex of the calixarenes showed different properties for the different cations, depending on the cations and the position of the substituent grafted on the ligand.